2022
DOI: 10.1590/0103-8478cr20210245
|View full text |Cite
|
Sign up to set email alerts
|

Plant extracts in agriculture and their applications in the treatment of seeds

Abstract: The harmful effects caused by the use of toxic substances in agriculture have led to the development of alternative solutions, and researchers have focused on understanding the effectiveness and potential of plant extracts in agriculture. The aim of this systematic review was to understand the situation of research and scientific dissemination, as well as how current science has approached the use of plant extracts in agriculture, especially in seed applications. There is potential on the use of plant extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…These phytochemical compounds are reported to inhibit the sporulation and mycelia growth of fungi [26,47]. Citrus extract has a bio-stimulant effect on seed germination, and therefore enhanced the germination of pearl millet seeds in this study [45].…”
Section: Application Of Seed Treatmentsmentioning
confidence: 54%
See 1 more Smart Citation
“…These phytochemical compounds are reported to inhibit the sporulation and mycelia growth of fungi [26,47]. Citrus extract has a bio-stimulant effect on seed germination, and therefore enhanced the germination of pearl millet seeds in this study [45].…”
Section: Application Of Seed Treatmentsmentioning
confidence: 54%
“…However, the citrus extract provided the most effect in reducing fungal incidence (24.6%) among the treatments. Both citrus and neem extracts contain antifungal properties which hindered the sporulation of fungal inoculum on the seeds [11,[44][45][46]. Das and Godbole [26] stated that aqueous or ethanolic extracts of neem and lemon have the potential to inhibit fungal growth due to the presence of phytochemical compounds including flavonoids, saponins, alkaloids, terpenoids and tannins in the extracts.…”
Section: Application Of Seed Treatmentsmentioning
confidence: 99%
“…Due to the recent growth in food demand, agricultural expansion, and increased crop productivity have resulted in a rise in the use of many synthetic products in the fields, which has created a number of issues for the environment, farmers, and consumers 78 . As a result, the use of plant biostimulants is a novel, ecologically friendly strategy for sustainable crop production, which is constrained by issues including water shortages, resource depletion, environmental stresses, and climate change 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This apparent effectiveness of the R. communis, A. indica and N. tabacum extracts could be attributed to its high contact toxicity effect on the larvae population growth in the first four weeks which overlapped with first and second sprays (see Figure 3) thereby reducing the leaf damage to maize in the early stages of the crop development. Based on performance alone, the use of plant extracts may exhibit varying levels of FAW control, and statistically lower mortality and damage rates compared to synthetic pesticides [26], but may nevertheless be an excellent alternative to synthetic pesticides. Besides being insecticidal, some of these plant leaf extracts like A. indica possess growth promoting substances, hence when applied before anthesis may boost grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested some plant extracts with insecticidal properties are effective and could be used by farmers against FAW [24,25]. However, most of these studies have been conducted either as a laboratory experiment or limited to a single season if it's a field study, as such the uptake of proven plant-based pesticides has remained small and further constrained by limited data on other beneficial aspects [26,27]. The acceptance and adoption of these technologies at the farm level are also hindered by a lack of data on the effectiveness of the farmers' experiential dose rate and spraying regimes and other plant health-related benefits such as reduction in the incidence and severity of maize ear rots.…”
Section: Introductionmentioning
confidence: 99%